Triphenylphosphine-assisted highly sensitive fluorescent chemosensor for ratiometric detection of palladium in solution and living cells. Issue 118 (12th November 2015) - Nie, Hailiang; Geng, Junming; Jing, Jing; Li, Yamin; Yang, Wen; Zhang, Xiaoling
Abstract : A triphenylphosphine-assisted highly sensitive fluorescent chemosensor for ratiometric detection of palladium in solution and living cells was developed. Abstract : Accurate and sensitive detection of palladium (Pd) is essential for both environmental and human health applications. This paper describes a triphenylphosphine (PPh3 )-assisted highly sensitive fluorescent chemosensor for ratiometric detection of Pd 2+ concentrations up to 300 nM with an LOD of 1 nM. During the detection, PPh3 plays a crucial role in improving the sensitivity of this chemosensor. The chemosensor also has suitable water-solubility which allows detection of Pd 2+ in solution. Our studies show that it exhibits excellent selectivity toward Pd 2+ and undergoes a color change from colorless to yellow to allow visual detection of Pd 2+ . Besides detection in solution, this chemosensor also shows great potential as an imaging reagent to detect Pd 2+ as low as 0.03 ppm in diverse cells.